Hadith #3387 - Sunan al-Nasa'i - al-J'd bin Dinar al-Yshkry الجعد بن دينار اليشكري; Anas ibn Malik; Ja'far bin Sulaiman al-Daba'i جعفر بن سليمان الضبعي; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل (Sunan al-Nasa'i)
“The Messenger of Allah stayed with Safiyyah bint Huyayy bin Akhtab on the way (back from) Khaibar for three days when he married her, then she was among those who were commanded to observe Hijab.”
Grade: